Prve literarne pravljice francoskega salonskega vala - Burcar, Lilijana (Primerjalna književnost, 2020)
Romantics introduced the notion that fairy tales are mere transcriptions or re-workings of folk tales, whose content they faithfully replicate. Literary history has proven otherwise: fairy tales are a hybrid literary genre that emerged out of the adaptations of basic features of two medieval and late renaissance genres, the Italian novels and medieval (knight and pastoral) romans. Narrative fram-ing was one of the structural features French salon writers took from the Italian novella, to which they added a technique of their own. Fairy-tales were preceded by dedicatory letters and introductions, and followed by afterwords and comments. These paratexts also carried literary references from earlier periods, which served as a source of inspiration for the fairy-tales' authors. From medieval courtly romans the authors took over the archetypal settings of aristocratic courts. These were disconnected from social environment, which resulted in the creation of geo-temporal distancing and static uniformity of the fairy-tale genre. To this generic mixture, the seventeenth-century French salon authors added elements of magic, which they borrowed from classical mythology and a special type of folk tale - a wonder tale with a special focus set on fairies, heroines' surrogate mothers.
Keywords: francoska književnost; hibridni žanri; literarne zvrsti; magično; novela; pastoralni roman; pravljica; romantika; viteški roman